1993
DOI: 10.2337/diacare.16.8.1146
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Benefit Analysis of Preconception Care for Women With Established Diabetes Mellitus

Abstract: Despite significantly higher per delivery costs for participants in a hypothetical preconception care program, intensive medical care before conception resulted in cost savings compared with prenatal care only. Third-party payers can expect to realize cost savings by reimbursing preconception care in this high-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
4

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 36 publications
0
38
0
4
Order By: Relevance
“…Extensive clinical studies have confirmed the need to start maternal metabolic treatment before or at the time of conception if the rate of fetal malformations is to be significantly reduced [1][2][3]. The absolute necessity for periconceptional care is now well accepted, however, the mechanism by which an early exposure to uncontrolled maternal diabetes could be carried-over to the organogenic phase remains to be elucidated [4].…”
Section: ]mentioning
confidence: 99%
“…Extensive clinical studies have confirmed the need to start maternal metabolic treatment before or at the time of conception if the rate of fetal malformations is to be significantly reduced [1][2][3]. The absolute necessity for periconceptional care is now well accepted, however, the mechanism by which an early exposure to uncontrolled maternal diabetes could be carried-over to the organogenic phase remains to be elucidated [4].…”
Section: ]mentioning
confidence: 99%
“…The risk of these outcomes may be minimized with preconceptional planning. Specifically, periconceptional folic acid supplementation and good glycemic control before pregnancy have been shown to reduce these risks to a level only slightly higher than that of the baseline population (2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Though delivering these services require huge amount of resources, the costs are nullified by the averted complications. 16,17 We have achieved a global consensus that preconception care is important as it addresses both maternal care and neonatal care.…”
Section: Preconception Care In Indiamentioning
confidence: 99%